MdJa2 Participates in the Brassinosteroid Signaling Pathway to Regulate the Synthesis of Anthocyanin and Proanthocyanidin in Red-Fleshed Apple - Su, Mengyu; Wang, Shuo; Liu, Wenjun; Yang, Ming; Zhang, Zongying; Wang, Nan; Chen, Xuesen (Frontiers in Plant Science, 2022)
Anthocyanin and proanthocyanidin play important roles in plant secondary metabolism. Although previous studies identified many transcription factors involved in anthocyanin and proanthocyanidin synthesis, the effects of MADS-box transcription factors are unclear in apple. In this study, we identified a MADS-box transcription factor, MdJa2, which contains a highly conserved MADS-box domain and belongs to the STMADS11 subfamily. Additionally, MdJa2 was responsive to BR signals, and the overexpression of MdJa2 inhibited the synthesis of anthocyanin and proanthocyanidin. Silencing MdJa2 in ‘Orin’ calli promoted anthocyanin and proanthocyanidin accumulations. Moreover, MdJa2 interacted with MdBZR1. MdJa2 was revealed to independently regulate anthocyanin and proanthocyanidin synthesis pathways. The MdJa2–MdBZR1 complex enhanced the binding of MdJa2 to the promoters of downstream target genes. Our research provides new insights into how MADS-box transcription factors in the BR signaling pathway control the accumulations of anthocyanin and proanthocyanidin in red-fleshed apple.